A Waste of Space? Controversies Surrounding the Working-Class Parlour in Inter-War Britain. (4th May 2018) - Cowman, Krista
Abstract: This article uncovers the fierce inter-war debate provoked by the British Government's decision to remove state subsidies for building larger "parlour-type" houses in 1923. Examining the various defences that were put forward in support of the working-class parlour it argues that the parlour was seen as a key marker of respectability in working-class communities with the potential to shape the behaviours and outlook of its inhabitants. Drawing on a variety of contemporary and autobiographical sources it suggests that the occasional use of the parlour, a keystone of its opponents' criticisms was precisely what gave most value to the room for its owners. Recent controversy over the bedroom tax in Britain suggests that "extra" space remains a contentious issue in subsidised homes today.